Investigation of testicular germ cell tumor on Cryptoorchidism with Hypospadia and Ambigous Genitalia - Amalia setyawati (Biomedical Engineering, 2015)
Objective: To identify germ cell malignancies and carcinoma in situ (CIS) in the gonads of high risk patientswith cryptorchidism and hypospadias (DSD cases) in Semarang as well as the frequency of OCT3/4 presence inthe case of germ cell malignancy.Methods: Specimens were examined for routine histopathology H&E staining. Immunohistochemistry stainingwas performed using antibody OCT3/4 and SCF to evaluate germ cells maturity and its progress towardmalignancies as well as its precursor lesion (CIS/GB).Result: We collected 33 specimens, however only 27 samples which qualified with categorization of GermTumor. Stage of differentiation tissue was varied categorized ranging from ovary, sex cord (tubae or funiculars).There were 7/26 samples with malignancies and precursor lesion.Conclusion: Genetic and environmental factors involve in the indirect role in the establishment of propermicro-environment for delayed maturation, transformation and progression of early germ cells. OCT3/4immunostaining is a promising and useful tool in managing patients known to be at high risk for thedevelopment of invasive GCTs.